2006
DOI: 10.1143/jjap.45.7105
|View full text |Cite
|
Sign up to set email alerts
|

CdS-Doped Glass as Dosimetric Material with Electron Spin Resonance

Abstract: Electron spin resonance (ESR) spectra have been measured in X-ray-irradiated CdS doped glass as functions of X-ray dose and effective X-ray energy. The intensity of the ESR signal is proportional to X-ray dose up to 40Gy. CdS-doped glass is more sensitive than a commercial alanine dosimeter. The intensity of the ESR signal decreases with decreasing effective X-ray energy for energies lower than 33 keV. Thermal stability was also studied.The ESR signal is relatively stable at room temperature. *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…In a previous paper, 2) we reported that an ESR signal was observed in X-ray-irradiated CdS-doped glass, Y-44, which contains CdS nanocrystals in silicate glass, and that Y-44 is more sensitive than bioglass and the alanine dosimeter. The intensity of the ESR signal increases with decreasing size of CdS nanocrystals in laser-irradiated CdS-doped glass.…”
mentioning
confidence: 85%
“…In a previous paper, 2) we reported that an ESR signal was observed in X-ray-irradiated CdS-doped glass, Y-44, which contains CdS nanocrystals in silicate glass, and that Y-44 is more sensitive than bioglass and the alanine dosimeter. The intensity of the ESR signal increases with decreasing size of CdS nanocrystals in laser-irradiated CdS-doped glass.…”
mentioning
confidence: 85%
“…The X-ray energy dependence of thermoluminescence is different from that of the induced absorption. On the other hand, X-ray energy dependence of the ESR signal intensity [8] is the same as that of thermoluminescence.…”
Section: Resultsmentioning
confidence: 75%
“…The sample investigated was commercial CdS-doped filter glass, Asahi Y-44. Thermoluminescence and ESR signal have been observed in the sample, 5,6) and the sample shows the most intense thermoluminescence in all the glasses investigated. The absorption edge of the glass was approximately 430 nm.…”
mentioning
confidence: 88%
“…2) We have reported that an electron spin resonance (ESR) signal 3) and thermoluminescence 4) are observed in X-ray-irradiated CdS-doped glasses. In previous papers, we reported the properties of thermoluminescence 5) and the ESR signal, 6) and we proposed that CdS-doped glass can be used as a material for radiation dosimetry with thermoluminescence and ESR. Here, we report the optical transmission spectra of X-ray-irradiated CdS-doped glass.…”
mentioning
confidence: 99%
See 1 more Smart Citation